Asia Rising : A Sectoral Perspective. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This paper undertakes a cross-country analysis of productivity growth at both the aggregate and sectoral level. It finds that Asia's remarkable output growth over the past 40 years reflected both high investment, and rapid productivity increases. These factors were in turn supported by the region's relatively strong institutional and policy environment, which encouraged resource shifts from low- to high-productivity sectors. Looking ahead, sustaining rapid growth requires meeting a number of key challenges: (i) implementing reforms to boost productivity in the increasingly important, but currently lagging, service sectors; (ii) providing policy support for continuing the shift of resources from agriculture to industry and services; (iii) strengthening policy frameworks in late-developing countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet